Analisis Pengadaan Logistik Alat Kesehatan di Rumah Sakit : Meningkatkan Kualitas Pelayanan Pasien - Khoirunnisa Ghefira Yusrani; Putri Regita Miolda; Keren Stelin Maliangkay; Resa Listiani; Syalisa Syabil; Endah Pravita Putri; Prasetio Hadi Pratama; Acim Heri Iswanto (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
The hospital is an important organization and is engaged in providing health services  that focus not only on medical service issues but also on non-medical service issues. The hospital guarantees the availability of medical devices to the availability of equipment that can affect the  quality of health services provided, including patient satisfaction. Therefore the purpose of this  study is to determine the analysis of the procurement of medical equipment logistics in hospitals.  The method used in this research is literature review from seven national journals obtained using  online database facilities via Google pages scholar and researchgate. The selected journal is based on its publication published from 2018-2023. The research results show that the analysis of logistics planning and procurement activities of medical devices in several hospitals in Indonesia  have various differences. The difference consists of hospitals that already have a plan logistics is good and some are not running perfectly. Procurement of medical devices that have not been good  due to several factors, one of which is an inadequate budget. So that management or logistics  management of medical devices is needed in hospitals so that medical devices are always available  in accordance with quality standards hospital health.